Performance and Environmental Assessment of Fired Clay Bricks Incorporating Industrial Ceramic Sludge - Intan Ume Roman Jufri; Aeslina Abdul Kadir; Sarani, Noor Amira (International Journal of Integrated Engineering, 2026)
The escalating environmental crisis and the rising volume of industrial waste have intensified the search for sustainable construction materials. Ceramic sludge, a by-product of the ceramic industry, poses a disposal challenge but also offers potential as a secondary raw material. This study investigates the incorporation of ceramic sludge into fired clay bricks and evaluates its effects on density, shrinkage, initial water absorption, compressive strength, and heavy metal leachability. Bricks were manufactured with ceramic sludge additions of 0%, 1%, 5%, 10%, 20%, and 30%, and tested in accordance with British Standard BS 3921:1985. The results indicate that ceramic sludge incorporation improved key performance parameters, with compressive strength reaching 25 N/mm², shrinkage remaining below 8%, density averaging 1800 kg/m³, and initial water absorption rates under 8 g/mm²·min, all within acceptable ranges. Heavy metal leachability, assessed using the Toxicity Characteristic Leaching Procedure (TCLP), showed that Pb, As, Zn, and Cu concentrations were well below the permissible limits set by the USEPA. In addition, bricks containing up to 30% ceramic sludge satisfied the SIRIM ECO 023:2016 eco-labelling requirement of incorporating at least 30% recycled content, confirming both structural performance and environmental compliance. These findings confirm that ceramic sludge can be successfully valorised in brick manufacturing, reducing dependence on virgin clay and diverting industrial waste from landfills.